The conveniently forgotten human rights of the Rohingya - Brinham, N (Refugee Studies Centre, University of Oxford, 2012)
As stateless Rohingya in Burma face containment in IDP camps and within their homes and communities in what is effectively segregation, their human rights are on the whole being ignored by countries keen either to support reform in Burma or to return refugees who have fled to their shores.